Review of Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference. - Lindner, Katharina (Transnational Cinemas, 2015)
On the 'Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference', held at the University of Hamburg, 14-15 October 2014, alongside the Hamburg International Queer Film Festival.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé